Consistent re-calibration of the discrete-time multifactor Vasicek model - Philipp Harms; David Stefanovits; Josef Teichmann; Mario V. Wüthrich (Risks, 2016)
The discrete-time multifactor Vasicek model is a tractable Gaussian spot rate model. Typically, two- or three-factor versions allow one to capture the dependence structure between yields with different times to maturity in an appropriate way. In practice, re-calibration of the model to the prevailing market conditions leads to model parameters that change over time. Therefore, the model parameters should be understood as being time-dependent or even stochastic. Following the consistent re-calibration (CRC) approach, we construct models as concatenations of yield curve increments of Hull-White extended multifactor Vasicek models with different parameters. The CRC approach provides attractive tractable models that preserve the no-arbitrage premise. As a numerical example, we fit Swiss interest rates using CRC multifactor Vasicek models.
Keywords: 330; interest rate model; re-calibration; HJM model; Vasicek model; Hull–White extension